The association between essential trace element (copper, zinc, selenium, and cobalt) status and the risk of early embryonic arrest among women undergoing assisted reproductive techniques - Cao, Yu; Liang, Chunmei; Shen, Lingchao; Zhang, Zhikang; Jiang, Tingting; Li, Danyang; Zou, Weiwei; Wang, Jieyu; Zong, Kai; Liang, Dan; Ji, Dongmei; Cao, Yunxia (Frontiers in Endocrinology, 2022)
Background Early embryonic arrest (EEA) leads to repeated cessation of fresh cycles among infertile women undergoing in vitro fertilization (IVF). Whether the levels of some essential trace elements [copper (Cu), zinc (Zn), selenium (Se) and cobalt (Co)] in the bodies of women are related to the risk of EEA warrants study. Objective Our study aimed to investigate the associations of peripheral blood levels of Cu, Zn, Se, and Co and their mixtures with the risk of EEA. Methods A total of 74 EEA cases (123 IVF cycles) and 157 controls (180 IVF cycles) from the reproductive center of the First Affiliated Hospital of Anhui Medical University in Hefei, China, between June 2017 and March 2020 were included in our study. Demographic and clinical data were collected from electronic medical records. Cu, Zn, Se, and Co levels were measured in blood samples collected on the day of oocyte retrieval when infertile women entered clinical treatment for the first time using an inductively coupled plasma mass spectrometer (ICP−MS). Generalized estimating equation (GEE) models were used to evaluate the associations of four essential trace element concentrations individually with the risk of EEA, and Bayesian kernel machine regression (BKMR) was used to explore the associations between four essential trace element mixtures and the risk of EEA. Results Se concentrations of infertile women were significantly lower in the case group compared with the control group. Co levels were significantly higher in the case group compared with the control group. The differences in Cu and Zn concentrations between the two groups were not significant. Based on single-metal models, Co was positively associated with the risk of EEA before and after adjustment for all confounders (odd ratio (OR) = 1.72, 95% confidence interval (CI): 1.18−2.52; OR = 2.27, 95% CI: 1.37−3.77, respectively), and Se was negatively associated with the risk of EEA before adjustment for all confounders (OR = 0.18, 95% CI: 0.07−0.51). BKMR analyses showed that Se was significantly and negatively associated with the risk of EEA when all the other three metals (Cu, Zn, and Co) were fixed at the 25th, 50th, or 75th percentiles, whereas Zn displayed a significant and positive association with the risk of EEA when all the other three metals (Cu, Se and Co) were fixed at the 25th, 50th, or 75th percentiles. Co did not show any effect on the risk of EEA when all the other metals (Cu, Zn, and Se) were fixed at the 25th, 50th, or 75th percentiles. In addition, an increasing trend of the joint effect of four essential trace elements on the risk of EEA was found, although it was not statistically significant. Conclusion The levels of essential trace elements (Cu, Zn, Se, and Co) might correlate with the risk of EEA to some extent. The present study might provide a real-world perspective on the relationship between essential trace elements and the risk of EEA when considering them as a single element or as mixtures.